2013
DOI: 10.4103/0971-9784.109770
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of intraoperative acute superior vena cava syndrome

Abstract: Acute intraoperative superior vena cava (SVC) syndrome is an exceedingly rare complication in the cardiac surgical population. We describe the case of a 71-year-old female undergoing multi-vessel coronary artery bypass grafting who developed acute intraoperative SVC syndrome following internal thoracic artery harvest retractor placement. Her symptoms included severe plethora, facial engorgement and scleral edema, which was associated with hypotension and severe elevation of central venous pressure. Transesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A review to determine the etiology of SVC syndrome found that the majority of benign cases are iatrogenic. These most often occur secondary to thrombosis associated with an intravascular device, catheter, or pacemaker wire [ 4 , 5 ]. Perioperative cases have been documented resulting from laceration of the SVC vessel during surgery [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review to determine the etiology of SVC syndrome found that the majority of benign cases are iatrogenic. These most often occur secondary to thrombosis associated with an intravascular device, catheter, or pacemaker wire [ 4 , 5 ]. Perioperative cases have been documented resulting from laceration of the SVC vessel during surgery [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only in rare cases have rapidly developing acute SVC syndromes been described. One such report describes an intraoperative occurrence secondary to a left internal thoracic artery retractor mechanically compressing the SVC [ 5 ]. In this case, we report an unusual instance of acute SVC syndrome secondary to stenosis caused by closure of the superior venous cannula used during cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%
“…However, SVC syndrome resulting from intraoperative cannulation for cardiopulmonary bypass was previously described in patients undergoing cardiac surgery. 8,9 Identification of SVC syndrome in adults treated with VV ECMO requires a high index of suspicion. In our case, we established the diagnosis based on our patient's physical examination, the point-of-care ultrasound findings, and a passive leg raise test.…”
Section: Discussionmentioning
confidence: 99%
“…However, SVC syndrome resulting from intraoperative cannulation for cardiopulmonary bypass was previously described in patients undergoing cardiac surgery. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac and thoracic surgery often involves extensive manipulation of intra-thoracic structures which increases susceptibility to SVC syndrome as well. A case of acute SVC syndrome during cardiac surgery was reported by Amundson et al [4]. During the surgery, the left internal thoracic artery (LITA) retractor was placed.…”
Section: Discussionmentioning
confidence: 99%